Faktor-Faktor yang Mempengaruhi Minat Pengguna Sistem Informasi Akuntansi Berbasis Dompet Digital - Salsa Gina Virginia; Elen Puspitasari (Ekonomis: Journal of Economics and Business, 2023)
The current development of digital technology not only opens up opportunities for new businesses to emerge, along with the development of the payment system in Indonesia is also the development of digital technology that we can meet. In making payment transactions, you can now use a system that has developed with technology. One system that can be applied in payment is the Accounting Information System. An electronic wallet (e-wallet) is an application that is useful as a means of digital payment based on internet technology. The selection of e-wallet products is influenced by the service features offered. This study aims to analyze what factors influence the interest in using a e-wallet based Accounting Information System. This research uses quantitative methods. The population of this study is all e-wallet application users. Determination of the sample using a purposive sampling technique with the criteria of respondents who have used or until now used the digital wallet application. Respondents obtained in this study were 259 respondents. Analysis of research data using SPSS version 21. The results of this study indicate that perceived convenience, perceived usefulness, perceived security, perceived risk, level of trust and financial literacy partially have a significant effect on interest in using a digital wallet-based Accounting Information System.